Profitability analysis of mango cultivation and its impact on farmer’s livelihood in some areas of Bangladesh (Bangladesh Journal of Agricultural Research, 2019)
The study was carried out to investigate profitability of mango farming and to assess the impact of BARI Aam-3 mango variety production on the farmer’s livelihood in four mango growing districts namely Khagrachori, Bandorban, Naogaon, and Satkhira of Bangladesh during February to March, 2018. A total of 128 BARI Aam-3 growers were selected using multi-stage random sampling technique. Descriptive statistics and financial profitability analysis was used to analyze data. The net return for one hectare of mango orchard was Tk. 730233 for 6-7 years of BARI Aam-3 mango orchard. Net present value was estimated to Tk. 444397 for BARI Aam-3 which indicates that mango cultivation fetches higher returns. The estimated benefit cost ratio was 2.01 for BARI Aam-3 which ensures that investment in BARI Aam-3 is feasible for the mango farmers. The BARI Aam-3 mango cultivation was also found to be a profitable enterprise since internal rate of return was very high (83.075%). The results also reveal that human capital increased by 54.34%, 68% and 60.54%; physical capital increased by 48.17%, 58% and 50% as well as social capital increased by 28.50%, 43% and 45.95% of the small, medium and large farmers respectively due to cultivation of BARI Aam-3 mango variety. Therefore, it is highly recommended to spread the information of BARI Aam-3 cultivation as a profitable enterprise among the mango growers throughout the country.Bangladesh J. Agril. Res. 44(1): 139-152, March 2019